ANALYSIS OF FACTORS AFFECTING THE S&P/OIC COMCEC 50 SHARIAH STOCK INDEX - Nani Suhartini; Ririn Tri Ratnasari; Shafinar Ismail (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2025)
Investors and policymakers in Islamic financial markets are expected to comprehend variables impacting the performance of Standard and Poor (S and P)/Organization of Islamic Cooperation (OIC) COMCEC 50 Islamic Stock Index. Therefore, this research aims to analyze the effects of S&P/OIC COMCEC 50 Islamic Stock Index on inflation, West Texas Intermediate (WTI) oil prices, United States Economic Policy Uncertainty (US EPU), and geopolitical risk (GPR). Autoregressive Distributed Lag (ARDL) model is used in the quantitative monthly data analysis spanning 2019-2023. The analysis estimates the adjustment rate toward long-term equilibrium using Error Correction Term (ECT). Furthermore, the short and long term links between global variables and S&P/OIC COMCEC 50 Index are analyzed. The results show that Islamic stock index benefits greatly from WTI oil prices over the long and short terms. Even though inflation and US EPU have no direct effects on the index, GPR shows a strong positive influence over the periods. However, the considerable ECT coefficient points to a quick adjustment process toward long-term equilibrium after external shocks. The significance of oil prices and geopolitical dynamics as major drivers of changes in Islamic financial markets is supported even though US EPU and worldwide inflation have a less significant effect. Based on the description, this research aimed to offer strategic recommendations for Islamic financial markets’ external risk management. Future research should incorporate other macroeconomic factors such as exchange rates, Islamic interest rates, and fiscal stability to understand the durability of Islamic financial index.